Food hygiene awareness and practices before and after intervention in food services in Montenegro. (March 2018) - Barjaktarović-Labović, Snežana; Mugoša, Boban; Andrejević, Vesna; Banjari, Ines; Jovićević, Ljiljana; Djurović, Dijana; Martinović, Aleksandra; Radojlović, Jasmina
Abstract: This two-stage interventional cross-sectional study was conducted with an aim to assess food handlers' knowledge on hygiene and food handling before and after the intervention in a form of education. The first stage of the study was conducted during a period November 2015 February 2016 in 32 randomly selected food services from all six cities at the Montenegrin seaside (N = 128). The study-specific structured questionnaire was developed. The percentage of correct answers ranged from a minimum of 10.2% to a maximum of 93.0%. The mean percentage score was 59.1 ± 2.7. The lowest level of knowledge was identified in relation to food storage conditions. The average level of knowledge was 22.7 ± 10.8 (15.6–35.2%). Only 15.6% of the study participants knew that food freezing does not eliminate the potential hazard due to various microorganisms. Generally, the results indicated poor knowledge of food handlers about hygiene and food safety in food services. Based on the obtained data the need for the second stage of the study, i.e. the necessity of the continuation of planned interventions was confirmed. After the training, correct answers ranged from 84.3% to 99.6%, and average level was 91.9 ± 5.3. When comparing the pre-test scores and post training test, t – test analysis showed high significant difference in the level of food safety knowledge (t = 0.000). Continuous education of food handlers from the aspects of good hygiene and food handling practice would significantly affect the number of foodborne diseases and could lead towards improved public health protection. Education could further promote the best practices in food services. Highlights: The training on food hygiene for foodhandlers is not mandatory in Montenegro. The level of knowledge of foodhandlers about hygiene and food safety was reported. This study reported a poor knowledge of foodhandlers in food services in Montnegro. Intervention in a form of education foodhandlers about food safety was carried out. The knowledge of employees in food services increased for 32.36% after treaning.